Desain dan Implementasi Sistem Informasi Akuntansi Berbasis Web untuk Analisis Kesehatan Keuangan Bank Wakaf Mikro Menggunakan Metode CAMEL - Eni Endaryati; Sukemi Kamto Sudibyo; Vivi Kumalasari Subroto; Siti Kholifah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The development of information technology encourages Islamic microfinance institutions to improve the effectiveness and transparency of financial management through digital information systems. However, Micro Waqf Banks still face problems in transaction management and financial reporting due to manual and unintegrated recording processes. This study aims to develop a web-based Accounting Information System integrated with the CAMEL method to support the financial health analysis of Micro Waqf Banks. The study uses a Research and Development (R&D) approach with a Waterfall model that includes needs analysis, design, implementation, testing, and system maintenance. The CAMEL method is used through the aspects of Capital, Asset Quality, Management, Earnings, and Liquidity. The results show that the system is able to improve the effectiveness of financial data management, accelerate report preparation, reduce recording errors, and produce an automatic financial health analysis. The validation results obtained a score of 3.5 from academic validators and 3.6 from practitioners with a very valid category. This study contributes to the integration of web-based accounting information systems and the CAMEL method in Islamic microfinance institutions.